1972
DOI: 10.1139/m72-011
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophages of Clostridium botulinum

Abstract: Temperate bacteriophages of diverse morphology were demonstrated by electron microscopy in toxigenic cultures of Clostridium botulinum. The 41 strains examined included 23 type E and multiple representatives of all other types. Cultures induced with mitomycin-C generally gave better yields, but phages were also demonstrable in untreated cultures.A provisional grouping of toxigenic types into four categories is suggested, based mainly upon associated phage patterns. Group 1 comprises types A, B, and F (all prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

1973
1973
2010
2010

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…Dolman and Chang [4], and Inoue and Iida [7] reported that strains selected arbitrarily from all types of C. botulinum produced phage particles in the culture through cellular lysis after the bacteria were treated with mitomycin C or UV irradiation. On the other hand, Betz and Anderson [3] could not detect any lysogenic strain among 25 strains of C. sporogenes examined.…”
mentioning
confidence: 99%
“…Dolman and Chang [4], and Inoue and Iida [7] reported that strains selected arbitrarily from all types of C. botulinum produced phage particles in the culture through cellular lysis after the bacteria were treated with mitomycin C or UV irradiation. On the other hand, Betz and Anderson [3] could not detect any lysogenic strain among 25 strains of C. sporogenes examined.…”
mentioning
confidence: 99%
“…In contrast, phage 5 has an elongated head and a flexible, sheathless tail resembling phages which infect C. sporogenes (Betz, 1968;Beatriz et al, 1981) or several strains of proteolytic types of C. botulinum (Eklund et al, 1969;Dolman & Chang, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…Many clostridia including neurotoxigenic species have been demonstrated to harbor bacteriophages (Dolman and Chang 1972;Eklund et al 1976Eklund et al , 1989Inoue and Iida 1968;Ogata and Hongo 1979). Research groups in the United States and in Japan demonstrated that bacteriophages mediated toxin production in C. botulinum types C and D (reviewed in Eklund et al 1989;Johnson 1997).…”
Section: Bacteriophagesmentioning
confidence: 99%